Ca2+ monitoring in Plasmodium falciparum using the yellow cameleon-Nano biosensor - Pandey, Kishor (2016)
Calcium (Ca2+)-mediated signaling is a conserved mechanism in eukaryotes, including the human malaria parasite, Plasmodium falciparum. Due to its small size (<10 μm) measurement of intracellular Ca2+ in Plasmodium is technically challenging, and thus Ca2+ regulation in this human pathogen is not well understood. Here we analyze Ca2+ homeostasis via a new approach using transgenic P. falciparum expressing the Ca2+ sensor yellow cameleon (YC)-Nano. We found that cytosolic Ca2+ concentration is maintained at low levels only during the intraerythrocytic trophozoite stage (30 nM), and is increased in the other blood stages (>300 nM). We determined that the mammalian SERCA inhibitor thapsigargin and antimalarial dihydroartemisinin did not perturb SERCA activity. The change of the cytosolic Ca2+ level in P. falciparum was additionally detectable by flow cytometry. Thus, we propose that the developed YC-Nano-based system is useful to study Ca2+ signaling in P. falciparum and is applicable for drug screening.